Experimental and Numerical Investigations of Fluid Flow Behaviors in a Biomass Cyclone Burner - Pasymi Pasymi; Yogi W Budhi; Yazid Bindar (ASEAN Journal of Chemical Engineering, 2020)
A combination of the experimental and numerical methods was used to investigate the fluid flow behaviors in a proposed cyclone burner. Recirculation flow and pressure drop, two of the important fluid flow behaviors that affect the burner's performance, have been studied here. Experimentally, the recirculation flow phenomenon in the burner was observed through paper slices dynamic in a transparent burner, and pressure drop was measured using a tube manometer. Meanwhile numerically, the fluid flow behaviors were simulated using the standard k-e turbulence model, under Ansys-Fluent software. The simulation results showed that, at a certain value of inlet aspect ratio (RIA) and initial tangential intensity (IIT), especially for high IIT, the recirculation flow phenomenon was clearly observed in the center of the burner cylinder which closely resembles a tornado-tail. The indication of existence recirculation flow was also found from the experiment results. The study also exhibited that the results of simulated static pressure drop were closely approaching the experiment results, particularly for IIT values £ 4.3. The mean deviation of static pressure between the simulation and the experiment results, for a varied range of RIA and IIT,was about 15%. From the results above, it was obvious that fluid flow behaviors (recirculation flow and static pressure) in the proposed cyclone burner are greatly influenced by the RIA and IIT values, where the IIT effect was more significant compared to the RIA. This study also suggests that, the standard k-e turbulence model could be relied upon to well predict the behaviors of fluid flow in the proposed cyclone burner, at low to moderate swirl intensities.